2010
DOI: 10.3233/npm-2010-0132
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose as an analgesic in relieving procedural pain in neonates

Abstract: Objective: This study was undertaken to study physiological and behavioral pain responses of neonates and to assess the analgesic effect of orally administered sucrose as assessed by the behavioral pain rating scale [DAN (Douleur Aiguë du Nouveau-né) score] during venepuncture in neonates. Method: In 50 healthy neonates requiring bilirubin estimation, blood sugar was randomly assigned to receive 2ml of 30% sucrose two minutes before the venepuncture (intervention) in comparison to a group not receiving sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The authors determined that non-nutritive sucking used together with music therapy reduced neonatal pain during heel-sticks [105]. Also, a number of studies demonstrated a beneficial effect of oral sucrose on neonatal procedural pain caused by heel-sticks, intramuscular injections, and venepunctures [107,108,109,110]. Further, Acharya et al published an article showing that oral sucrose not only reduced pain in term but also preterm infants [111].…”
Section: Acute Procedural Pain and Anxiety: A Complex Issuementioning
confidence: 99%
“…The authors determined that non-nutritive sucking used together with music therapy reduced neonatal pain during heel-sticks [105]. Also, a number of studies demonstrated a beneficial effect of oral sucrose on neonatal procedural pain caused by heel-sticks, intramuscular injections, and venepunctures [107,108,109,110]. Further, Acharya et al published an article showing that oral sucrose not only reduced pain in term but also preterm infants [111].…”
Section: Acute Procedural Pain and Anxiety: A Complex Issuementioning
confidence: 99%
“…PICO question comparisons that were prioritised by the NPGG in their discussions were those involving breastfeeding, oral sugar, expressed breastmilk, skin-to-skin care, and non-nutritive sucking. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ...…”
Section: Resultsmentioning
confidence: 99%
“…58 studies (n=3948) directly compared oral sugar solutions with placebo or no intervention. 24 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 50 (86%) studies showed sugar to be superior in narrative synthesis, 24 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , …”
Section: Resultsmentioning
confidence: 99%